Intervertebral disc degeneration—Current therapeutic options and challenges - Samanta, Ankita; Lufkin, Thomas; Kraus, Petra (Frontiers in Public Health, 2023)
Degeneration of the intervertebral disc (IVD) is a normal part of aging. Due to the spine's declining function and the development of pain, it may affect one's physical health, mental health, and socioeconomic status. The majority of intervertebral disc degeneration (IVDD) treatments today focus on the symptoms of low back pain rather than the underlying etiology or mechanical function. The deteriorated disc is not entirely recovered by the conservative or surgical treatment that corrects symptoms and structural abnormalities. To enhance the clinical outcome and the quality of life of the patient, several therapeutic modalities have been created. The purpose of this study is to review earlier studies that addressed potential novel approaches for deteriorated disc repair. In this review, we provide a succinct explanation of IVD and various causes of IVDD including genetic, nutritional, environmental, and mechanical factors. We also describe numerous conservational and promising modern therapeutic techniques like small molecules, stem cell therapy, exosomes, and scaffold-based treatment for degenerated discs, including their applicability in a clinical environment and relevance to the degeneration process